Mid-infrared ethene detection using difference frequency generation in a quasi-phase-matched LiNbO3 waveguide. - Grilli, R; Ciaffoni, L; Hancock, G; Peverall, R; Ritchie, G; Orr-Ewing, A (Optical Society of American (OSA), 2009)
A periodically poled LiNbO3 (PPLN) crystal waveguide has been used to produce up to 200 microW of mid-infrared light around 3081 cm(-1) with a wide tunability range of approximately 35 cm(-1). Two commercial near-infrared diode lasers at 1.064 microm (pump) and 1.583 microm (signal) are mixed in a nonlinear optical crystal to achieve difference frequency generation. The 48 mm long directly-bonded quasi-phase-matched (QPM) PPLN waveguide shows a conversion efficiency of 12.3% W(-1). Applications in trace gas detection have been demonstrated for ethene, using multipass absorption coupled with wavelength modulation spectroscopy, and cavity enhanced absorption spectroscopy with a lock-in detection scheme: bandwidth reduced sensitivities of alpha(min)=8 x 10(-9) and 1.6 x 10(-8) cm(-1) Hz(-1/2)(2sigma), respectively, have been achieved.